QUICK DIAGNOSIS OF JAPANESE ENCEPHALITIS FOR NEW DIAGNOSED EMERGING DISEASE USING PCR TECHNIQUE IN SURABAYA, INDONESIA - Matondang, Muhammad Qushai Y.; Nasronudin, Nasronudin; Aksono, Eduardus Bimo; Lusida, Maria Inge; Nastri, Aldise Mareta; Fajar, Nur Syamsiatul; Jannah, Lilis Mundri (Indonesian Journal of Tropical and Infectious Disease, 2013)
Background: Japanese enchepalitis (JE) is a viral disease that considered as zoonotic disease, which transmitted through mosquito vectors that had JE virus. Mainly caused by the mosquito C. Tritaeniorhynchus (the most important vector is the mosquito Culex, which feeds on cattle in preference to human). JE virus disease can also cause disturbances in the central nervous system eg. brain, bone marrow, and meninges which has serious impact on public health. This disease has been reported from Japan, Korea, Taiwan, India, Myanmar, Thailand, Western Pacific and Southeast Asia to Indonesia. However, the incidence of this disease in Indonesia has not been well known in various animal species or humans. Aim: The purpose of this study is to develop rapid diagnostic examinations on patient diagnosed JE virus in Surabaya by using PCR (Polymerase Chain Reaction). Because, JE disease can lead to dead-end at the patient if not treated immediately. Method: The research methods, extraction method, PCR (1stÂ RT-PCR and 2ndÂ Nested PCR) are conducted using Japanese encephalitis PCR detection kit. Result: The results of the examination showed that 2 out of 17 people (11,765%) are positive with PCR bands 227 bp (basepair). This diagnostic technique to determine and to deal with early onset of the disease. Solutions for preventive actions can be started from the termination of the cycle vectors to vaccination measures. Conclusion: For his own medical factors given to reduce fever and swelling and reduce the pain.